Evolution of Organizational Scale and Scope - Arnoud W.A. Boot; Todd T. Milbourn; Anjan V. Thakor (Tinbergen Institute, 2002)
This paper examines the determinants of organizational scale and scope, with applications to various industries, including financial services. We build a model in which new opportunities arise for firms, but the skills needed to exploit them effectively are unknown. Early investments in these new opportunities expand scope and allow firms to learn the skills needed to make more efficient production decisions later on. The value of early scope expansion is thus increasing in the strategic uncertainty about the skills needed for future success in exploiting new opportunities. The disadvantage of early scope expansion is that it requires irreversible investments before actual demand is known. This demand uncertainty means potential losses since the investment cannot be recovered when demand does not materialize. Thus, early entry into a new activity involves a tradeoff, and this tradeoff works in favor of early entry under two conditions. First, there must be sufficiently high strategic uncertainty about the skills needed for success in the new activity. Second, the firm 's existing operations must be sufficiently profitable to give it the necessary deep pockets to absorb the potential loss of the capital invested early if there is no demand. This perspective allows us to link the optimality of scope expansion to the degrees of competition in the firm's existing activities as well as the new activity, and the development of the capital market. Moreover, to the extent that a scale-expanding merger deepens the firm's pockets, scale expansion will facilitate scope expansion and thus precede it.
Keywords: 330; Theorie der Unternehmung; Investitionsentscheidung; Markteintritt; Unternehmenswachstum; Produktdifferenzierung; Evolutionsökonomik; Theorie